Pediatric oral and dental health knowledge in child development students - Belen Sirinoglu Capan; Saniye Selin Doger; Buse Tansu Gundogan; Didem Elitez (Acta Scientiarum. Health Sciences, 2024)
Oral and dental problems can also affect general health. The aim of this study is to evaluate the senior child development undergraduate students' knowledge on pediatric oral and dental health and to examine the changes in their knowledge levels after the training. A 24-item questionnaire was sent to the participating students, in which their demographic characteristics and their knowledge about children's oral health were questioned. Afterwards, 3-hour training was given and the same questionnaire was sent again at the end of the training. One-way Anova and Mann-Whitney-U tests were used to compare quantitative variables. Fortysix students participated in this study. The students' knowledge score was 7.65±1.95 before the training; it was calculated as 9.78±2.06 after training. The difference was statistically significant (p < 0.05). The majority of the incorrect answers before the training were given for fluoride toothpaste use (78.3%), tooth brushing start period (60.9%), first permanent tooth eruption time (43.5%), and treatment option of caries in primary teeth(41.3%). A significant decrease was observed in these rates after the training (p < 0.05). Child development students have a moderate knowledge on oral and dental health and their knowledge levels increase with training. In order to raise children with better oral health habits, the undergraduate education of the Child Development Department needs to be rearranged.